Pálido, pero sereno: the return of the protagonist from migration and migrancia - Cangalaya Sevillano, Luis Miguel (2020)
The present investigation analyzes the topic of the return from the perspective of the protagonist of the novel Pale, but serene of Carlos Eduardo Zavaleta. It is a migrant subject who returns to the place of origin, despite its multiple displacements in three main spaces: the province, the capital and abroad. For the analysis, two categories are taken as the basis: migration as a social phenomenon and migrancia, based on the theory of Abril Trigo. It is concluded that the migrant subject maintains a close and permanent relationship between praxis (here-now) and memory (there-then) and, therefore, his return is necessary and even always motivated by the cultural and family elements that revolve around his conception of the world.